2018
DOI: 10.1007/s13314-018-0327-0
|View full text |Cite
|
Sign up to set email alerts
|

First record of White clover cryptic virus-2 in New Zealand

Abstract: White clover cryptic virus-2 is recorded for the first time in New Zealand in three commercial cultivars of white clover: Grasslands Huia, Grasslands Kopu II and Grasslands Sustain. An RT-PCR assay was used to amplify and sequence a~590 bp fragment of the coat protein gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Taking multiple virus infections as an example, follow-up studies should be conducted to understand the host response to single and multiple infections. Plant health risk assessment should actually be carried out for every HTS detected virus more especially that there is evidence of the existence of cryptic [ 139 , 140 , 141 ] and even beneficial viruses [ 142 ]. The availability of scientific knowledge as such will enable plant health, policymakers and regulators to make correct decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Taking multiple virus infections as an example, follow-up studies should be conducted to understand the host response to single and multiple infections. Plant health risk assessment should actually be carried out for every HTS detected virus more especially that there is evidence of the existence of cryptic [ 139 , 140 , 141 ] and even beneficial viruses [ 142 ]. The availability of scientific knowledge as such will enable plant health, policymakers and regulators to make correct decisions.…”
Section: Discussionmentioning
confidence: 99%
“…One study found active replication of a Secovirus in honey bees (Li et al 2014), yet the results are debated and additional experiments are needed to support the findings (Miller et al 2014). White clover cryptic virus 2 is the only dsRNA virus we found in this study and has only recently been recorded in New Zealand (Guy and Gerard 2018). The virus has rarely been found in insects, although WCC2 has been detected in bumble bees (Pascall et al 2019).…”
Section: Discussionmentioning
confidence: 63%